Study guide [to] Fundamentals of anatomy & physiology - Martini, Frederic (Benjamin Cummings, 2005)
ver the years, Charles Seiger's Study Guide has helped thousands of students master key concepts in anatomy and physiology. It includes a variety of review questions, including multiple-choice, labeling, and concept mapping organized by the three-level system used in the text